Formulação e implementação de estratégias do Programa de Assistência Estudantil: um estudo de caso em uma instituição pública de Sergipe - Dantas, Cristiane Feitoza (2017)
Organizations construct and deconstruct their activities in order to establish their permanence in the market. This is a continuous cycle, and it is analyzed by the field of organizational strategy that studies the organizational change and the sustainability. It is understood that it is not easy to adapt to organizational changes, since it takes a lot of commitment and dedication to understand the environment and then to make strategic decisions that are appropriate to the organizational objectives. The way in which the strategic positions of an organization are influenced by its decision processes and its administrative systems portrays the strategic process. Studying the strategic decision provides a challenge in finding appropriate theories and methodologies to harmonize the more proactive issues of the unique strategic decision and the boundaries pointed out by the environment in which the organization finds itself. Faced with this, the purpose of this study was to investigate the process of formulation and implementation of the strategies of the student assistance program in a public institution in Sergipe. Theoretical basis were strategic process, the formulation and implementation of strategies and a brief outline of student assistance. The research is qualitative, exploratory and descriptive. The research strategy used was the single case study. In order to maximize learning, the case was chosen intentionally and by accessibility. Data were collected through semi-structured interviews, documents and non-participant observation and were analyzed through content analysis. As for the results obtained, the existence of both deliberate and emergent strategies was evidenced, the harmony between the exploration and the exploitation with the disciplined imagination was also evidenced. It was perceived that the implementers execute well the strategies planned by the formulators, but it was verified that there is no effective control of the implementation of the strategies by the formulators. There was also a lack of strategic feedback and resistance in the strategic implementation process.